Identification of cisplatin-binding sites on the large cytoplasmic loop of the Na(+)/K(+)-ATPase - Šeflová, Jaroslava (J Enzyme Inhib Med Chem, 2018)
Cisplatin is the most widely used chemotherapeutic drug for the treatment of various types of cancer; however, its administration brings also numerous side effects. It was demonstrated that cisplatin can inhibit the Na(+)/K(+)-ATPase (NKA), which can explain a large part of the adverse effects. In this study, we have identified five cysteinyl residues (C452, C456, C457, C577, and C656) as the cisplatin binding sites on the cytoplasmic loop connecting transmembrane helices 4 and 5 (C45), using site-directed mutagenesis and mass spectrometry experiments. The identified residues are known to be susceptible to glutathionylation indicating their involvement in a common regulatory mechanism.